THE EFFECT OF USING DIGITAL MIND MAPPING ON STUDENTS’ READING COMPREHENSION ABILITY AT SMPN 2 RAMBAH SAMO - Syifa Aulia; Fadly Azhar; Mahdum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using digital mind mapping on students' reading comprehension ability in recount texts. This study uses a pre-experimental method with one group pre-test post-test. The research sample consisted of eighth-grade students at SMPN 2 Rambah Samo in the 2025/2026 academic year. The research instrument was a multiple-choice test consisting of 32 questions that had been tested for validity and reliability (Cronbach's Alpha = 0.974). The data were analyzed using normality tests, paired sample t-tests, and N-Gain. The results showed an increase in students' reading comprehension skills after using digital mind maps. The average pre-test score was 58.93, while the post-test score was 67.36. The Sig. value (two tails) was 0.000 < 0.05, so Ha was accepted. Thus, digital mind maps have a significant effect on students' reading comprehension ability.